Variations in lipid levels according to menstrual cycle phase: clinical implications. (April 2011) - Mumford, Sunni L; Dasharathy, Sonya; Pollack, Anna Z; Schisterman, Enrique F
Understanding variations in lipoprotein cholesterol levels throughout the menstrual cycle is important because there may be clinical implications regarding the appropriate timing of measurement and implications on the design and interpretation of studies in women of reproductive age. Our objective was to review the evidence comparing lipoprotein cholesterol levels throughout the menstrual cycle among premenopausal women. Overall, lipoprotein cholesterol levels were observed to vary in response to changing estrogen levels. Taken together, the evidence suggests that total cholesterol and LDL-C tend to be highest during the follicular phase and to decline during the luteal phase, with HDL-C highest around ovulation. Based on these findings, the menstrual cycle phase should be taken into account when evaluating lipoprotein cholesterol levels among reproductive-aged women. Measuring cholesterol levels during menses is recommended for consistent comparisons as this phase can be more reliably identified than other phases, although women within National Cholesterol Education Program acceptable ranges, but near the boundaries when tested during menses, should undergo additional tests.